Do Politicians Use Implicature for Nonsense? An Analysis Of 2024 U.S Presidential Debate - Khoirul Barriyah (LINGUISTICA, 2025)
Implicature was firstly coined as a strategy to create effective communication. It works differently when it has come to politicians. This study investigates the implicature used by Donald Trump and Kamala Harris in the first 2024 U.S presidential debate focused on war issues. A qualitative descriptive approach was employed to explore how the candidates used implicature and its use in political discourse. The result showed that both candidates violated Gricean theory of maxims to create implicature to hide and imply their real meaning. It is common in political discourse especially in presidential debate. This study was limited to war issue. Further research might be needed to investigate two areas; political implicature itself and war issues.